2017
DOI: 10.1080/20469047.2017.1281094
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of uropathogens isolated from Cambodian children

Abstract: Background: Bacterial resistance to commonly used antimicrobials is an increasing problem in Asia but information concerning the antimicrobial susceptibility of bacteria causing urinary tract infections (UTIs) in children is limited. Methods: This was a 5-year retrospective study of children with suspected UTI attending a paediatric hospital in north-west Cambodia. Urines with a positive culture containing a single organism with a count of w10 5 colony-forming units (CFU)/ml were considered diagnostic of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
(7 reference statements)
2
9
0
Order By: Relevance
“…In our study, the overall prevalence of ESBL-producing pathogens is 26.8 %, and the most common causative organisms were E.coli (66.93%), (32.4%), were ESBL, and Klebsiella Species (9.84%), (32%) were ESBL. This is comparable to other countries with prevalence in India of 37.7% [13], Iran 30.5% [14,15], Cambodia 44% [16], and Turkey 41% [17].…”
Section: Discussionsupporting
confidence: 74%
“…In our study, the overall prevalence of ESBL-producing pathogens is 26.8 %, and the most common causative organisms were E.coli (66.93%), (32.4%), were ESBL, and Klebsiella Species (9.84%), (32%) were ESBL. This is comparable to other countries with prevalence in India of 37.7% [13], Iran 30.5% [14,15], Cambodia 44% [16], and Turkey 41% [17].…”
Section: Discussionsupporting
confidence: 74%
“…To date, there are no published reports of CPE/K in humans or livestock in Cambodia or of community carriage of ESCE/K in Cambodia. However, ESCE/K isolates have been detected as causative pathogens in Cambodian patients (Caron et al, ; Emary et al, ; Moore et al, ; Rammaert et al, ; Vlieghe et al, ). Genetic characterization of ESBL‐producing E. coli isolates in bloodstream infections in Cambodia revealed that 96% were of CTX‐M‐type, mainly bla CTX‐M‐15 and bla CTX‐M‐14 (Vlieghe et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing concern, however, about the antibiotic resistance of uropathogens due to improper and extensive use of antibiotics. Resistance to trimethoprim‐sulfamethoxazole (TMP‐SMX) and cephalosporins, which are primarily preferred in empiric treatment, is rapidly increasing . It is also of concern that the prevalence of UTI with extended spectrum beta‐lactamase‐producing (ESBL (+)) enteric bacteria also has been increasing worldwide .…”
mentioning
confidence: 99%